2020
DOI: 10.1186/s12957-020-02039-8
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term outcomes after colonic self-expandable metal stent placement for malignant large-bowel obstruction as a bridge to surgery focus on the feasibility of the laparoscopic approach: a retrospective, single center study

Abstract: Purpose Malignant large-bowel obstruction (MLBO) is a highly urgent condition in colorectal cancer with high complication rates. Self-expandable metal stent (SEMS) placement in MLBO is a new decompression treatment in Japan. Preoperative stent placement (bridge to surgery: BTS) avoids emergency surgery, but oncological influences of stent placement and post-BTS surgical approach remain unclear. We examined short- and long-term results of surgery for MLBO after SEMS placement in our hospital. Methods We retro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Recent studies found that after SEMS placement as BTS therapy, the laparoscopic approach can be a safe alternative to ES, if the procedure is applied precociously [ 29 ]. Since the first case of laparoscopic surgery in the BTS group on 2012-08-27 in our center, we can now carry out combined organ resection for obstructive colorectal cancer patients with liver metastasis after successful stent decompression, under laparoscopic approach [ 30 ] or minimally invasive small incision [ 31 ]. The BTS group proceeded to resection at a median of 18.5 days (14, 29 days) post-stenting, with a confirmation of malignant histology by biopsy [ 32 ] and without anastomotic leak observed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found that after SEMS placement as BTS therapy, the laparoscopic approach can be a safe alternative to ES, if the procedure is applied precociously [ 29 ]. Since the first case of laparoscopic surgery in the BTS group on 2012-08-27 in our center, we can now carry out combined organ resection for obstructive colorectal cancer patients with liver metastasis after successful stent decompression, under laparoscopic approach [ 30 ] or minimally invasive small incision [ 31 ]. The BTS group proceeded to resection at a median of 18.5 days (14, 29 days) post-stenting, with a confirmation of malignant histology by biopsy [ 32 ] and without anastomotic leak observed.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have reported different technical success rates (90.5%-98%) of SEMS stent placement ( 6 , 28 31 ). In our center, the success rate is close to 96%.…”
Section: Discussionmentioning
confidence: 99%